Prevalence and Mechanisms of Partial Migration in Ungulates - Berg, Jodi E.; Hebblewhite, Mark; St. Clair, Colleen C.; Merrill, Evelyn H. (Frontiers in Ecology and Evolution, 2019)
Partial migration, a phenomenon wherein only some individuals within a population migrate, is taxonomically widespread. While well-studied in birds and fish, partial migration in large herbivores has come into the spotlight only recently due to the decline of migratory behavior in ungulate species around the world. We explored whether partial migration in ungulates is maintained at the population level through frequency-dependence, an environmental-genetic threshold, or a conditional strategy. Through a review of studies describing individual variation in migratory behavior, we then addressed how density-dependent and -independent factors such as social constraints, competition for forage, and escape from predators or pathogens, alone or together, could lead to occurrence of both migrants and residents within a population. We searched for evidence that intrinsic and extrinsic factors could combine with genetic predispositions and individual differences in temperament or life experience to promote migratory tendencies of individuals. Despite the long-held assumption for ungulates that migration is a fixed behavior of individuals, evidence suggested that flexibility in migratory behavior is more common than previously thought. Partial migration maintained by a conditional strategy results in changes in movement tactics as state-dependent responses of individuals. Data are needed to empirically demonstrate which factors determine the relative costs and benefits to using migratory vs. resident tactics. We outline what types of long-term data could address this need and urge those studying migration to meet these challenges in the interest of conserving partially migratory populations.